Unlocking renewable energy potential: Overcoming barriers and accelerating the transition - Apramadha, Made Sandra; Prasetyo, Randy Teguh (Institute for Advanced Social, Science, and Sustainable Future, 2025)
Background: Indonesia's energy transition is driven by increasing energy demands, economic growth, and the urgent need to mitigate climate change. Despite being endowed with abundant renewable energy resources, the country faces significant challenges in shifting from a fossil-fuel-dominated energy mix to a more sustainable one. While Indonesia has vast potential in solar, wind, hydro, biomass, geothermal, and ocean energy, the adoption of renewable energy remains limited. This paper seeks to understand the barriers hindering renewable energy development in Indonesia and identify opportunities to accelerate the transition. Methods: This study uses Systematic Literature Review (SLR) with the PRISMA protocol to analyze renewable energy in Indonesia, using sources from Google Scholar and Science Direct. Literature selection based on relevance, quality, and recency, resulted in 37 publications that were analyzed narratively to identify challenges, developments, and potential of renewable energy in Indonesia. Findings: The results reveal that Indonesia’s renewable energy utilization is significantly below its potential, contributing less than 10% to the energy mix. Major barriers include economic feasibility concerns, regulatory and policy inconsistencies, insufficient financial and technical support, and a heavy reliance on coal. Additionally, the study highlights substantial renewable energy resources available, such as the 443 GW potential from various sources, which remain largely untapped. Conclusion: Achieving Indonesia's renewable energy targets requires addressing these barriers through clear and consistent policies, improved regulatory frameworks, and enhanced financial and technical support. The study suggests leveraging the country’s geographical advantages and diverse renewable resources to significantly contribute to a sustainable energy future. Novelty/Originality of this article: This study provides a comprehensive analysis of Indonesia’s renewable energy challenges and opportunities using a systematic approach. By quantifying the untapped 443 GW potential and identifying specific barriers, it offers insights into strategic policy measures and investment directions to accelerate the country’s transition to sustainable energy.